Can artificial intelligence be decolonized?. (3rd April 2021) - Adams, Rachel
ABSTRACT: AI is altering not only local and global society, but what it means to be human, or, to be counted as such. In the midst of concerns about the ethics of AI, calls are emerging for AI to be decolonized. What does the decolonization of AI imply? This article explores this question, writing from the post-colony of South Africa where the imbrications of race, colonialism and technology have been experienced and debated in ways that hold global meaning and relevance for this discussion. Proceeding in two parts, this article explores the notion of de/coloniality and its emphasis on undoing legacies of colonialism and logics of race, before critiquing two major discontents of AI today: ethics as a colonial rationality and racializing dividing practices. This article develops a critical basis from which to articulate a question that sits exterior to current AI practice and its critical discourses: can AI be decolonized?